Publishing Activities of Ivan Lypa in Odesa: "O. L. S." in the History of Ukrainian Book Printing (Book Science Aspect of the Fund of the Odesa National Scientific Library). - Yatsun , Nadiia (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
Research aim. The aim of the study is to analyze the publishing activities of Ivan Lypa in Odesa, particularly the role of the publishing house Odeska Literaturna Spilka ("O. L. S.") [Odesa Literary Union], its contribution to the development of Ukrainian book printing, and the formation of the national cultural space. Special attention is given to the characteristics of "O. L. S." publications held in the collection of the Odesa National Scientific Library. Methodology of the research. The methodological foundation of the article is the historical-biographical method, which made it possible to study Ivan Lypa’s activities as a publisher, his contribution to the cultural process, and his connections with the intellectual environment of that time. It also allowed for an analysis of the establishment and development of the "O. L. S." publishing house, determining its place and role in Ukrainian book printing. A source studies approach ensured the examination of primary sources, contemporary reviews, and publications that shed light on the publishing house’s activities. The application of the comparative-historical method helped outline the role of "O. L. S." in the development of Ukrainian printing. Content analysis facilitated the study of the publications’ content, determining their genre specifics, thematic features, and ideological directions. Bibliographical analysis contributed to the examination of the distinctive features of "O. L. S." publications in the collection of the Odesa National Scientific Library, particularly their printing characteristics, artistic design, content, typographic execution, and their role in the development of early 20th-century Ukrainian literature. Special attention is given to the study of provenance: copies with inscriptions, bookplates, and ownership or institutional stamps have been identified, allowing for the tracing of the history of each book monument over time and space until its acquisition by the Odesa National Scientific Library. The scientific novelty of the study lies in the clarification of the period of activity of "O. L. S.", which lasted from 1902 to 1912. The list of its publications has been expanded, in particular, it has been supplemented with publications that were not previously mentioned. In the process of the study, the authorship of one of the publications, which was previously considered anonymous, was established: based on the analysis of bibliographical sources, it was found out that its author is B. Grinchenko. For the first time, a bibliographic analysis of copies stored in the funds of the Odesa National Scientific Library has been carried out. This allows to popularize the library fund and determines its historical and cultural value. The bibliographic study reveals the significant personal contribution of Ivan Lypa to the development of publishing in Odesa, in particular, his activities as a publisher, editor and popularizer of Ukrainian books. Relevance. The study of the publishing activities of Ivan Lypa and Odeska Literaturna Spilka [Odesa Literary Union] expands knowledge about the history of Ukrainian book printing, revealing the contribution of the first Ukrainian publishing house in Odesa at the beginning of the 20th century. The analysis of copies from the ONNB fund allows us to trace their historical and cultural value. In the context of modern war and attempts by Russian propaganda to belittle the role of Odesa as a Ukrainian cultural center, revealing the city’s national heritage is important for restoring historical justice. The study of Ivan Lypa’s experience as a publisher demonstrates the significance of local initiatives in the development of Ukrainian printing, literature, and public movements, which remains relevant today. Conclusions. Odesa Literary Union became the first Ukrainian publishing house in Odesa at the beginning of the 20th century. Analysis of the publications of "O. L. S." confirms not only their literary, but also significant historical and cultural value for the study of the history of Ukrainian book printing. Their uniqueness lies in the combination of literary and artistic value, historical significance and connection with the political and cultural processes of their time. The connection with the personal book collection of Mikhail Komarov emphasizes the role of the intelligentsia in preserving the national heritage and allows us to trace the continuity of cultural traditions in Odesa. Research into Ivan Lypa’s publishing activities in Odesa, in particular based on materials from the Department of Rare Editions and Manuscripts of the Odesa National Scientific Library, allows us to gain a deeper understanding of his role in the development of Ukrainian culture. Ivan Lypa is an extraordinary figure who combined the roles of a writer, cultural, public and political figure and publisher. In the conditions of imperial bans and censorship restrictions, he found opportunities to publish Ukrainian literature, spread the national idea and support cultural progress. His publishing activities not only preserved spiritual heritage, but also inspired future generations to preserve and multiply Ukrainian culture. In the modern context, Lypa’s experience as a publisher is a valuable example of how local initiatives can contribute to the development of publishing, literary creativity, public movement, and all-Ukrainian cultural revival. Thanks to his efforts to create and distribute Ukrainian publications, Odesa became one of the leading centers of the Ukrainian national movement. This not only emphasizes the significance of Lypa’s figure for the history of Ukrainian culture, but also proves that Odesa is a Ukrainian city, despite Russian propaganda narratives aimed at concealing its Ukrainian history and cultural heritage.